Synchronous N‐S and E‐W extension at the Tibet‐to‐Himalaya transition in NW Bhutan. Issue 7 (6th July 2015) - Cooper, F. J.; Hodges, K. V.; Parrish, R. R.; Roberts, N. M. W.; Horstwood, M. S. A.
Abstract: Despite ~50 Myr of continuous continent‐continent collision, contractional structures in the Himalayan‐Tibetan orogen are today limited to the northern and southern margins of the system, while extension dominates much of the interior. On the Tibetan Plateau, Cenozoic E‐W extension has been accommodated by strike‐slip faults and extensional grabens, while N‐S extension at the Tibet‐to‐Himalaya transition has been accommodated by the South Tibetan fault system (STFS). The genetic relationship between N‐S and E‐W extension is disputed, although age constraints indicate temporal overlap of at least 7 Myr. In NW Bhutan the two intersect where the STFS basal detachment is cut by the Yadong cross structure (YCS), an extensional half graben that provides a rare opportunity to constrain relative timings. We report U‐Pb zircon dates from four STFS footwall leucogranites consistent with episodic magmatism during the middle‐late Miocene and in situ U(‐Th)‐Pb monazite and xenotime dates from three metasedimentary rocks ranging from late Oligocene to middle Miocene. We suggest that amphibolite facies footwall metamorphism was ongoing at the time the basal STFS detachment initiated as a ductile structure in the middle‐late Miocene. Late‐stage granitic intrusions may reflect footwall melting during extensional exhumation along the STFS, but post‐metamorphic and post‐intrusion fabrics suggest that most displacement occurred after emplacement of the youngest granites. Some of the oldest YCS‐related fabrics are found in a deformed 14 Ma leucogranite, implying middle Miocene ductile deformation. This observation, along with evidence for subsequent brittle YCS deformation, suggests that N‐S and E‐W extensional structures in the area had protracted and overlapping deformation histories. Key Points: Relationship between N‐S and E‐W extension in Himalayan‐Tibetan orogen is unclear In NW Bhutan, N‐S and E‐W extensional structures intersect Both sets of structures had protracted and overlapping deformation histories